THE INFLUENCE OF FINANCING TO DEPOSIT RATIO (FDR), NON PERFORMING FINANCING (NPF) AND CAPITAL ADEQUACY RATIO (CAR) ON PROFITABILITY (ROA) OF SHARIA BANKING IN INDONESIA - Erwan Aristyanto; Adi Mulyono (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
This research aims to analyze the influence of Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Capital Adequacy Ratio (CAR) on the Profitability of Sharia Banking in Indonesia as proxied by Return On Assets (ROA). This research is quantitative research. The population used is the annual reports of all Sharia Commercial Banks in Indonesia during the 2014-2018 period. The sample selected used the purposive sampling method and the sample obtained was 6 Sharia Banks. In this research, the analysis used is multiple linear regression analysis using IBM SPSS Statistics version 21 software. Based on the results of multiple linear regression from this research, it shows that simultaneously the dependent variable (ROA) can be explained by independent variables consisting of FDR, NPF, and CAR. Partially, the NPF variable has a negative and significant effect on ROA. while the FDR and CAR variables have a positive and insignificant effect on ROA.